Promoting Social Welfare: Maqasid Sharia Compliance of Indonesian Hajj Financial Manegement Agency’s Maslahat Program - Hidayat, Rahmat (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
BPKH (Hajj Financial Management Agency) was established based on the mandate of Law Number 34 of 2014 concerning Hajj Financial Management. The purpose of managing hajj finances is to improve the quality of hajj service management, the rationality and efficiency of Hajj Pilgrimage Costs (BPIH), and the welfare of Muslims. To achieve the three goals above, BPKH implements welfare programs in the form of corporate social responsibility (CSR) or "philanthropy" programs that must be in line with Maqaṣid al-Sharia. Based on the results of the study, the welfare programs and activities designed and implemented from 2018 to 2022 have been fully in line with Maqaṣid al-Sharia, so they need to be continued, strengthened, refined, and their scope expanded by complying with the provisions of laws and regulations and the principles of governance, risk, and compliance (GRC) to provide benefits for the Muslim community. BPKH (Badan Pengelola Keuangan Haji) dibentuk berdasarkan amanat Undang-Undang Nomor 34 Tahun 2014 tentang Pengelolaan Keuangan Haji. Tujuan pengelolaan keuangan haji adalah untuk meningkatkan kualitas pengelolaan pelayanan haji, rasionalitas dan efisiensi Biaya Penyelenggaraan Ibadah Haji (BPIH), dan kemaslahatan bagi umat Islam. Untuk mencapai ketiga tujuan di atas, BPKH melaksanakan program-program kemaslahatan berupa program tanggung jawab sosial perusahaan (CSR) atau “filantropi” yang harus selaras dengan Maqaṣid al-Sharia. Berdasarkan hasil kajian, program dan kegiatan maslahat yang dirancang dan dilaksanakan sejak tahun 2018 sampai dengan tahun 2022 telah sepenuhnya selaras dengan Maqaṣid alSharia, sehingga perlu dilanjutkan, diperkuat, disempurnakan, dan cakupannya semakin diperluas dengan mematuhi ketentuan peraturan perundang-undangan dan prinsip tata kelola, risiko, dan kepatuhan (GRC) untuk memberikan kemaslahatan bagi masyarakat muslim.